معوقات استخدام التسويق الالكتروني في تسويق وثائق التامين العراقية: دراسة تطبيقية في عدد من شركات التامين العراقية (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The emergence of the Internet made it possible to provide new financial products and services in different packages and also led to a fundamental change in the business environment by reaching any person, as the geographical distance was no longer limited. In recent years, a new method of marketing services has emerged, based mainly on information technology, and it is called electronic marketing or electronic commerce. This method represented a major challenge in the activities of organizations, and they began to rely on it to achieve clear progress and superiority over their competitors, which prompted all organizations to seriously think about developing marketing its services to keep pace with these developments. In the era of the Internet, institutions have become able to interact directly with changes in the markets within a few minutes. This has forced Iraqi insurance companies to adopt a marketing strategy characterized by flexibility to interact quickly with these variables in the business environment. This is because the Iraqi insurance service differs from the rest of the intangible services surrounding Iraqi society. From the lack of insurance awareness on the one hand, and from the developments that the world has witnessed in recent years in the field of communications technology in wide fields on the other hand.This study included a general introduction that clarified the nature of the Iraqi insurance service and aimed to identify the factors that limit the use of electronic marketing in marketing Iraqi insurance documents by extrapolating the point of view of a group of workers within Iraqi insurance companies and a group of ordinary people in Iraqi society.The study concluded that the new challenge facing Iraqi insurance companies requires them to shift from traditional methods in their dealings with individuals to new, advanced and accelerating methods of growth. The results also showed that there is an impact for all variables of the study in reducing the use of electronic marketing in Iraqi insurance companies because this type of services has This privacy differs from the marketing of other services due to the presence of many factors, some of which pertain to the insurance companies themselves and some of which pertain to the Iraqi individualThe study also addressed electronic marketing, how to plan and manage access to it, and the challenges facing it in Iraqi society.  The study also recommended the necessity of spreading insurance awareness within Iraqi society and the extent of its importance in reducing risks in an environment where danger is more widespread than others, given the circumstances that Iraq is going through, and increasing electronic awareness on the other hand to achieve the success of marketing insurance trust in Iraq.